2011
DOI: 10.1016/j.bcp.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren affects fatty-acid uptake and lipid-related genes in rodent and human cardiomyocytes

Abstract: 2 ABSTRACT PURPOSE: We investigated whether the direct renin inhibitor aliskiren can affect metabolism in cardiomyocytes from rat, mouse and human sources. METHODS AND RESULTS: At 10-50µmol/L, aliskiren significantly increased medium-chain-fatty-acid uptake in primary-cultured neonatal-rat and HL-1 adult-mouse-derived cardiomyocytes (BODIPY-induced fluorescence intensity). The fatty-acid transporter CD-36 was correspondingly translocated to, but the glucose transporter Glut-4 away from, the sarcoplasmic reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, microarray analysis of the complete genome of aliskiren-treated neonatal-rat cardiomyocytes, with RT-qPCR and immunoblot confirmation assays in rat and human primary cardiomyocytes, revealed that aliskiren upregulated mRNA and increased protein expression of several enzymes that play an important role in cholesterol breakdown [31].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, microarray analysis of the complete genome of aliskiren-treated neonatal-rat cardiomyocytes, with RT-qPCR and immunoblot confirmation assays in rat and human primary cardiomyocytes, revealed that aliskiren upregulated mRNA and increased protein expression of several enzymes that play an important role in cholesterol breakdown [31].…”
Section: Discussionmentioning
confidence: 99%
“…(15,(26)(27)(28) In the present study concentrations of aliskiren in the micromolar range were found to be safe for RPE cells and therefore were used to…”
Section: Discussionmentioning
confidence: 99%
“…In our results, DRI reduced the expression of intracellular renin after ischemia in DM heart. Aliskiren has been reported to reduce the gene expression of cardiovascular diseases-related proteins including connective tissue growth factor (CTGF) and tissue growth factor-β (TGF-β) [36,37]. Aliskiren also reduced the gene expression of (pro)renin receptor in the kidney of in vivo diabetic model of mouse-renin expressing rat 2+ (TG(mRen-2)).…”
Section: Renin Contributes To Ischemic Tolerance In Diabetic Heartmentioning
confidence: 99%